THE EFFECT OF COMPRESSIBILITY FOR DISPLACEMENT NOISE FROM THE HELICOPTER ROTOR - B. S. Kritskiy; R. M. Mirgazov; A. A. Nikolskiy (Научный вестник МГТУ ГА, 2016)
The problem of noise generation of rotor due to the thickness of blades - displacement noise is considered. The method of calculating the displacement noise, which is based on linear acoustic theory for the changes in the effective thickness of the blade over time due to the compressibility of the flow are described.